Synthesis of Indoles by Palladium‐Catalyzed Reductive Cyclization of β‐Nitrostyrenes with Carbon Monoxide as the Reductant. Issue 26 (3rd August 2015) - Ferretti, Francesco; EL‐Atawy, Mohamed A.; Muto, Stefania; Hagar, Mohamed; Gallo, Emma; Ragaini, Fabio
Abstract: An efficient catalytic cyclization of β‐nitrostyrenes to indoles was developed. The reaction was applied to the synthesis of 3‐arylindoles and 2‐alkylindoles. Given that in the latter case the starting β‐nitrostyrenes can be easily obtained by a Henry reaction, the present method allows indoles to be obtained in a two‐step sequence starting from cheap reactants. Abstract : Indoles and azaindoles can be obtained by reductive cyclization of β‐nitrostyrenes, which can be easily obtained in most cases from cheap nitroalkanes and aromatic aldehydes. The method is effective for the synthesis of both 2‐ and 3‐substituted indoles; Phen = 1, 10‐phenanthroline.